Bionics inspired modified two-dimensional MXene composite membrane for high-throughput dye separation. Issue 4 (August 2021) - Lin, Qingquan; Liu, Yongcong; Zeng, Guangyong; Li, Xiaoke; Wang, Bin; Cheng, Xiaojie; Sengupta, Arijit; Yang, Xiaojun; Feng, Zhenhua
Abstract: Membrane separation technology has been widely used in the field of industrial dye wastewater treatment. In this work, a series of new composite membranes were fabricated by modifying MXene two-dimensional (2D) materials with polydopamine (PDA) from the mussel biological inspiration via vacuum filtration on cellulose acetate (CA) support. Scanning electron microscope (SEM), transmission electron microscope (TEM), atomic force microscope (AFM), X-ray diffraction technique (XRD), energy spectrum analysis (EDS), have been utilized to evident the successful synthesis of MXene and the modification of MXene by PDA. The resultant PDA@MXene/CA membrane was found to have good hydrophilicity, and the pure water flux reached up to 271.2 L·m −2 ·h −1, which was 277% more than the unmodified membrane. An improvement in dye separation capability has also been noticed using PDA@MXene/CA membranes. The rejection ratio of direct red 28 reached 88.9%, and that of direct black 38 reached 88.6%. Moreover, a strong anti-fouling characteristic with good antibacterial ability of resultant membrane was demonstrated. Therefore, the new modified membrane showed the potential for good application prospects in the field of small molecule separation. Graphical Abstract: ga1 Highlights: The PDA@MXene/CA composite membrane was constructed by vacuum filtration. The composited membrane exhibited ultra-high flux and good rejection for dyes. The antibacterial and recycling ability of membrane were improved significantly.